ANALYSIS OF THE ROLE OF LEADERSHIP IN IMPROVING THE EFFECTIVENESS OF GOVERNMENT PROGRAMS AT THE NORTH MANDREHE DISTRICT OFFICE, WEST NIAS REGENCY - Kalvin Armen Lahagu; Meiman Hidayat Waruwu; Eliagus Telaumbanua; Palindungan Lahagu (Jurnal Ilmiah METADATA, 2026)
This study aims to analyze the role of sub-district head leadership in improving the effectiveness of government program implementation at the North Mandrehe District Office, West Nias Regency. The study used a descriptive qualitative approach, with data collection methods including observation, in-depth interviews, and documentation. The research informants consisted of the sub-district head, sub-district secretary, section heads, sub-district staff, and village heads. The research results show that sub-district leadership plays a significant role in increasing the effectiveness of government programs through the application of a participatory and collaborative leadership style. The sub-district head functions as a coordinator, motivator, facilitator, and supervisor in program implementation, involving sub-district officials and the community at every stage of planning, implementation, and evaluation. The contribution of leadership is seen in improved cross-stakeholder coordination, accelerated program realization, more optimal resource management, and increased staff motivation. However, program implementation still faces several challenges, including limited infrastructure, regional accessibility, human resource capacity, and low community participation in several villages. This study concludes that adaptive, communicative, and participatory sub-district leadership can improve the effectiveness of government programs at the sub-district level. Therefore, strengthening leadership capacity and increasing synergy among stakeholders is necessary to achieve more optimal public services and regional development.